1995
DOI: 10.1016/0014-5793(95)01329-6
|View full text |Cite
|
Sign up to set email alerts
|

Precise mapping of the tms1 binding site on p53

Abstract: Originally identified as multicopy suppressor of a lethal growth arrest caused by expression of a tumour mutant cDNA of p53 in fission yeast the tmsl gene product was found to form stable complexes with p53 in yeast. By using purified recombinant proteins multimeric complexes of tmsl and p53 could be demonstrated and recently the p53 binding site on the tmsl protein was established to the sequence YYITTEDFCT (aa 116-125) in the vicinity of a well conserved cell division motif. Here we report the precise mappin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 32 publications
0
12
0
Order By: Relevance
“…This is in good agreement with our identi®ed p34 cdc2 binding domain spanning from amino acid 334 ± 339. Interestingly, the same domain has been identi®ed previously as binding domain of the ®ssion yeast protein tms1 (Wagner, 1994;Wagner et al, 1995b) which had been isolated as a multi copy suppressor of a p53-induced growth arrest in ®ssion yeast (Wagner et al, 1991(Wagner et al, , 1993. In addition, the corresponding region was found to be critical for the association of the b-subunit of protein kinase CK2 with p53 suggesting the identi®cation of an important new functional domain on the p53 protein (Wagner et al, 1994a;Appel et al, 1995).…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…This is in good agreement with our identi®ed p34 cdc2 binding domain spanning from amino acid 334 ± 339. Interestingly, the same domain has been identi®ed previously as binding domain of the ®ssion yeast protein tms1 (Wagner, 1994;Wagner et al, 1995b) which had been isolated as a multi copy suppressor of a p53-induced growth arrest in ®ssion yeast (Wagner et al, 1991(Wagner et al, , 1993. In addition, the corresponding region was found to be critical for the association of the b-subunit of protein kinase CK2 with p53 suggesting the identi®cation of an important new functional domain on the p53 protein (Wagner et al, 1994a;Appel et al, 1995).…”
Section: Discussionmentioning
confidence: 75%
“…This method allows the rapid solid phase synthesis of peptides in equal molar quantities immobilised on a cellulose membrane in a format suitable for systematic analysis of proteinprotein interactions or antibody epitope mapping. This method had already proven successful for the mapping of the p53 binding site on the tms1 protein (Wagner, 1994;Wagner et al, 1995a) and vice versa (Wagner et al, 1995b) as well as the precise de®nition of the epitopes of three dierent monoclonal antibodies raised against recombinant tms1 protein (Wagner et al, 1994b;Schneider et al, 1995). First we synthesized a set of 11 overlapping peptides of 10 amino acid long sections of the p53 primary amino acid sequence spanning the p34 cdc2 binding region from amino acid 285 ± 344.…”
Section: The P34mentioning
confidence: 99%
“…In addition, these residues are hydrophobic (Fig. 5, C and D) and have been proposed to be a potential site for interaction with other proteins (33,34). Residues Gly 334 and Arg 335 are also surface-exposed, and they belong to the turn that links the ␣-helices to the ␤-sheets.…”
mentioning
confidence: 99%
“…For example, Lomax et al (1998) have shown that both L344P and R337C have reduced ability to bind to MDM2 which forms a negative feedback regulatory loop with p53. Other proteins such as tms1 (Wagner et al, 1995) and p34 cdc2 (Wagner et al, 1998) interact with residues in the tet domain spanning the R337C mutation site. The occurrence of these two mutations in familial cancers underlines the important role the tet domain plays in p53 function.…”
mentioning
confidence: 99%